Algebra Examples

Find the Perpendicular Line y=(5x+1)/3 ; (1,1)
y=5x+13 ; (1,1)
Step 1
Find the slope when y=5x+13.
Tap for more steps...
Step 1.1
Rewrite in slope-intercept form.
Tap for more steps...
Step 1.1.1
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Step 1.1.2
Split the fraction 5x+13 into two fractions.
y=5x3+13
Step 1.1.3
Reorder terms.
y=53x+13
y=53x+13
Step 1.2
Using the slope-intercept form, the slope is 53.
m=53
m=53
Step 2
The equation of a perpendicular line must have a slope that is the negative reciprocal of the original slope.
mperpendicular=-153
Step 3
Simplify -153 to find the slope of the perpendicular line.
Tap for more steps...
Step 3.1
Multiply the numerator by the reciprocal of the denominator.
mperpendicular=-(1(35))
Step 3.2
Multiply 35 by 1.
mperpendicular=-35
mperpendicular=-35
Step 4
Find the equation of the perpendicular line using the point-slope formula.
Tap for more steps...
Step 4.1
Use the slope -35 and a given point (1,1) to substitute for x1 and y1 in the point-slope form y-y1=m(x-x1), which is derived from the slope equation m=y2-y1x2-x1.
y-(1)=-35(x-(1))
Step 4.2
Simplify the equation and keep it in point-slope form.
y-1=-35(x-1)
y-1=-35(x-1)
Step 5
Write in y=mx+b form.
Tap for more steps...
Step 5.1
Solve for y.
Tap for more steps...
Step 5.1.1
Simplify -35(x-1).
Tap for more steps...
Step 5.1.1.1
Rewrite.
y-1=0+0-35(x-1)
Step 5.1.1.2
Simplify by adding zeros.
y-1=-35(x-1)
Step 5.1.1.3
Apply the distributive property.
y-1=-35x-35-1
Step 5.1.1.4
Combine x and 35.
y-1=-x35-35-1
Step 5.1.1.5
Multiply -35-1.
Tap for more steps...
Step 5.1.1.5.1
Multiply -1 by -1.
y-1=-x35+1(35)
Step 5.1.1.5.2
Multiply 35 by 1.
y-1=-x35+35
y-1=-x35+35
Step 5.1.1.6
Move 3 to the left of x.
y-1=-3x5+35
y-1=-3x5+35
Step 5.1.2
Move all terms not containing y to the right side of the equation.
Tap for more steps...
Step 5.1.2.1
Add 1 to both sides of the equation.
y=-3x5+35+1
Step 5.1.2.2
Write 1 as a fraction with a common denominator.
y=-3x5+35+55
Step 5.1.2.3
Combine the numerators over the common denominator.
y=-3x5+3+55
Step 5.1.2.4
Add 3 and 5.
y=-3x5+85
y=-3x5+85
y=-3x5+85
Step 5.2
Reorder terms.
y=-(35x)+85
Step 5.3
Remove parentheses.
y=-35x+85
y=-35x+85
Step 6
 [x2  12  π  xdx ]